Medumba language use by non-natives: factor of social integration or singularity - NGO NDJEYIHA, Madeleine; NGAMI KAMAGOUA, Jeff Sterline (PT. Antis International Publisher, 2023)
The increasing and diversified internal mobility in the periurban and rural areas of Cameroon leads to a proliferation of cultures and a close contact between native and migratory languages. In such a plurilingual context, the coexistence of languages, practices and varieties with varying status and symbolism can be a source of dynamisation or alteration of the autochthonous languages whose intergenerational transmission is challenged by a defy of originality. This article examines the sociolinguistic impact of Medumba language use by non-natives, thereby addressing the following question: what is the sociolinguistic impact of Medumba language use by non-natives ? The theory of interactionism which examines the interaction between language and society in order to understand the language practices resulting from situations of languages in contact, frames this study. It argues that the permanent contact between languages and the interaction between their speakers have a considerable impact on their structures and uses. The analysis is based on previous work, verbal interactions and oral information collected through direct observation techniques, surveys and semi-structured interviews with informants. It reveals that, Medumba language use by non-native speakers leads to the emergence of a composite language, representing an hybrid variety that incorporates the differents cultural and social realities of the non natives communities. The use of those composite languages represents a communicative strategy implemented by non-natives to preserve their culture thereby ensuring communication with natives for “un meilleur vivre ensemble”.